Analysis of the impact of international crude oil price fluctuation on Chinese stock market - Wang, Jingyu (2022)
This paper aims to study the impact of international crude oil price changes on China's energy-related stocks and finds a dynamic relationship between the two over time, and a structural change occurred in 2018. Before 2018, the oil price shock had a significant positive impact on the Chinese stock market. The impact effects on different types of energy-related stocks such as oil and gas, coal, electricity and new energy are all significant and positive. The impact coefficient of oil price shock on coal and power stocks is the largest, and the impact degree of new energy industry stocks is slightly lower.